The impact of nutrition education on nutrition knowledge and adherence to the mediterranean diet in adolescent competitive swimmers - Philippou, E.; Middleton, N.; Pistos, C.; Andreou, E.; Petrou, M. (Journal of Science and Medicine in Sport, 2017)
Objectives: Nutrition education of adolescent competitive swimmers is under-studied although their diet and nutrition knowledge are generally poor. This study aimed to assess the impact of nutrition education on nutrition knowledge and adherence to the Mediterranean Diet (MD) and explore the effect of parental education on the swimmers` MD adherence. Design: A pre-post measurement interventional study was carried out. Methods: A half-day nutrition education session was delivered for the swimmers and a separate session for their parents. At baseline and 6-weeks post-workshop, a short nutrition knowledge assessment of food sources of nutrients and the MD composition as well as adherence to the MD using the KIDMED Index were undertaken. The swimmers` parents also completed the KIDMED Index to evaluate the swimmers` diet. Results: Thirty-four competitive swimmers (age: 15.2 ± 1.5 yr, 23 males) and 22 of their parents participated in the study. There was an improvement in MD adherence with 47% having good adherence post-intervention vs 21% at baseline (p < 0.01) and an increase in the KIDMED Index score (median [interquartile range]: 5.0 [4.0-7.0] vs 7.0 [7.0-9.0]; p < 0.01)). There was also an increase in the swimmers` nutrition knowledge assessment score (median [IQR]: 7.0 [5.0-8.0] vs 7.0 [6.0-8.0], p < 0.05)), and a trend for a lower score post-intervention in swimmers whose parents did not participate compared to those whose parents participated (6.0 [6.0-7.8] vs 7.0 [7.0-8.0], p = 0.063). Conclusions: The intervention improved adherence to the MD and increased nutrition knowledge. The findings support parental participation in nutrition education.